2000
DOI: 10.1002/(sici)1097-4547(20000201)59:3<301::aid-jnr3>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Early cortical precursors do not undergo LIF-mediated astrocytic differentiation

Abstract: Multipotential stem cells have been isolated from the developing and adult CNS. Similar identified factors control the differentiation of these cells. A striking example is the instructive action of CNTF/LIF activating the JAK/STAT pathway to induce astrocytic differentiation in both fetal and adult CNS stem cells. Here we show that E12 cortical precursors express functional LIF receptors but do not exhibit this differentiation response to CNTF/LIF either in explant or in dissociated cell culture. The lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
64
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 43 publications
6
64
0
Order By: Relevance
“…2 Thus, early neural progenitors preferentially differentiate into neurons and do not respond properly to astrocyte-inducing cytokines, at least in part due to DNA methylation of astrocyte-characteristic genes such as glial fibrillary acidic protein (GFAP). 3,4 In line with these observations, it has been shown that loss of the DNA methyl transferase DNMT1 results in hypomethylation and precocious onset of astrocytic genes at the expense of neurogenesis in early neural precursors. 5 In later progenitors, astrocytic genes become demethylated.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…2 Thus, early neural progenitors preferentially differentiate into neurons and do not respond properly to astrocyte-inducing cytokines, at least in part due to DNA methylation of astrocyte-characteristic genes such as glial fibrillary acidic protein (GFAP). 3,4 In line with these observations, it has been shown that loss of the DNA methyl transferase DNMT1 results in hypomethylation and precocious onset of astrocytic genes at the expense of neurogenesis in early neural precursors. 5 In later progenitors, astrocytic genes become demethylated.…”
mentioning
confidence: 64%
“…5 In later progenitors, astrocytic genes become demethylated. 3,4 Transcriptional repression of astrocytic genes and thus the correct numbers of progenitors and neurons at these late events, instead depends on other factors such as the Notch-regulated transcription factor CSL/RBP-Jk and the co-repressors N-CoR and SMRT. 6,7 In addition, neurogenic members of the basic helix-loop-helix (bHLH) family of transcription factors, such as Mash1 and Neurogenin (Ngn) 2, interferes with astrocyte differentiation in multipotent neural progenitors at least in part by sequestering the coactivators CBP/p300 required for astrocyte differentiation.…”
mentioning
confidence: 99%
“…LIF signaling activates the Jak (Janus kinase)/STAT (signal transducer and activator of transcription) and MAP (mitogen-activated protein) kinase pathways, which promote astrogliogenesis in vitro (Bonni et al, 1997;Molne et al, 2000;Viti et al, 2003;Chang et al, 2004;Barnabe-Heider et al, 2005;He et al, 2005). In addition, LIF is well known for promoting mouse embryonic stem (ES) cell selfrenewal (Williams et al, 1988) and the long-term growth of embryonic human NSCs in culture (Wright et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of a single proneural basic helix-loop-helix (bHLH) transcription factor, neurogenin-1 (Ngn1), which specifies neuronal fate and is highly expressed only in the cortical germinal zone during the neurogenic period, determines whether BMPs promote neuronal or glial differentiation 12 . Other astroglial-inducing factors, such as leukemia inhibitory factor (LIF), Notch-Delta, and basic fibroblast growth factor (bFGF) can initiate the astrocyte differentiation program only in E15 or older cortical progenitors, not in early (for example, E11), neurogenic progenitors 8,[13][14][15][16][17][18][19] . In E11 CNS neural progenitors, both Notch-Delta and bFGF function instead as pro-proliferation and anti-differentiation factors 15,18,[20][21][22] .…”
mentioning
confidence: 99%
“…It was previously postulated that the Jak-STAT pathway is fully active in early neural progenitors. The failure of activated STAT1/3 to initiate glial gene transcription in neurogenic progenitors has been attributed to STAT-independent inhibitory mechanisms 8,13 . Evidence against this hypothesis has come from the findings that factors inhibiting gliogenesis during the neurogenic period, such as the pro-neural bHLH factors (for example, Ngn1 and Ngn2) and DNA methylation, not only inhibit STAT1/3 from activating glial genes, but also suppress the phosphorylation and activation of the Jak-STAT pathway 12 (data not shown).…”
mentioning
confidence: 99%